Zastosowanie wybranych metod graficznych do konstrukcji planów eksperymentu - Peternek, Piotr (Application of Some Graphical Methods for Construction of Experimental Plans, 2007)
In construction of fractional factorial experimental plans prior knowledge or experience can suggest which effects should be estimated unconfounded with any main effect or interaction. Very useful to obtain such plans could be graphical techniques. The article presents two graphical methods of construction plans: linear graphs proposed by Taguchi and graph aided method suggested by Wu and Chen. Both methods were compared on example. The author indicated additional possibility of modification graph aided method to achieve plans with multilevel factors.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1167, s. 206-219